PROGRAMA DE EDUCAÇÃO NUTRICIONAL PARA A TERCEIRA IDADE - Pereira, Bruna; De Carli, Eliane (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
The increase in life expectancy expands in such a way that a large part of the current population will reach old age due to the consequences of technological advances and better living conditions. The aging process brings several physiological changes that consequently compromise the nutritional status, increasing the risk for the development of chronic diseases. Regarding changes in eating habits of elderly Brazilian consumer groups with higher levels of education and access to information, they have established a relationship between healthy eating practices and disease prevention. Evaluate the eating conditions of 50 seniors who participated in the program of the University of the Third Age – Unoesc – São Miguel do Oeste. The theme of healthy eating was proposed to work through the use of a questionnaire to assess the quality of food for the elderly in the UNITI program at UNOESC/São Miguel do Oeste. 50 seniors, who participated in the university program for the third age, answered the questionnaire consisting of twenty questions, filling out the form on healthy eating, online. As for the amount of meals eaten daily, 24 of the participants reported having three to four meals a day, which is within the Brazilian average; fruits consumed per day, 36% of participants said eating 3 or more 36% and 12% reported consuming 2 and 1; 54% reported consuming fish only a few times a year, 24% consume it from one to four times a week; 68% of respondents said they consume whole milk. It is concluded that most elderly people are aware of the importance of food in the stage of life in which they are.